2012
DOI: 10.1093/jmt/49.2.205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relaxation Music Listening on Sleep Quality in Traumatized Refugees: A Pilot Study

Abstract: These results support the use of relaxation music listening at bedtime to improve sleep quality in traumatized refugees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…The pQoL reflects aspects of bodily self‐image, negative and positive feelings, self‐esteem and personal beliefs. This result is consistent with other studies on music and sleep that have reported improvements in mood and well‐being (Harmat et al., ; Jespersen & Vuust, ). The effect of music on well‐being and quality of life is important as daytime impairment is often the main concern of persons with insomnia and the reason for seeking treatment (Morin & Benca, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The pQoL reflects aspects of bodily self‐image, negative and positive feelings, self‐esteem and personal beliefs. This result is consistent with other studies on music and sleep that have reported improvements in mood and well‐being (Harmat et al., ; Jespersen & Vuust, ). The effect of music on well‐being and quality of life is important as daytime impairment is often the main concern of persons with insomnia and the reason for seeking treatment (Morin & Benca, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we included objective measures of sleep using actigraphy and PSG, and baseline measures revealed few severe disturbances of these sleep aspects in our sample. Mean WASO resembled the values found in insomnia populations, whereas TST and SE seemed less affected (Baglioni et al, 2014 (Harmat et al, 2008;Jespersen & Vuust, 2012). The effect of music on well-being and quality of life is important as daytime impairment is often the main concern of persons with insomnia and the reason for seeking treatment (Morin & Benca, 2012).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In previous trials, the Minimal Clinically Important Difference (MCID) on PSQI was considered 2.5 scale points. This trial aims to detect a clinically important difference between TAU and add-on treatment and not merely a statistically significant difference and hence MCID was set to 2.5 scale points on the PSQI and the within-groups standard deviation was set to 3 scale points [ 68 ]. With a power of 90% and alpha 0.05 we estimated a sample size for each group of 32 and a total of 128.…”
Section: Methodsmentioning
confidence: 99%
“…Estos textos ponen de manifiesto la capacidad de la música de expresar los malestares sociales o su potencial de denuncia y movilización de grupos sociales a partir de su emisión (Al-Taee, 2002;Gray, 2010;Ibrahim & Shepler, 2011;Pinto, 2014;Rolston, 2001), pero sin ser realizada por las comunidades víctimas de la violencia ni dentro de un proceso colectivo en la comunidad. Del mismo modo, tampoco se incluyeron (3) estudios donde se usó la música desde una perspectiva terapéutica con un enfoque clínico explícito (Bakker, Blokland, May, Pauw & Breda, 1999;Carr et al, 2012;Choi, 2010;Curtis, 2012;Fairweather, 2002;Jespersen, 2012;Rankin, 1999). La razón que motivó esta exclusión fue la necesidad de centrar el estudio en la perspectiva psicosocial y su enfoque comunitario.…”
Section: Metodologíaunclassified